2017
DOI: 10.1021/acs.chemmater.7b03862
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Useful Hole–Electron Dopants in SnO2

Abstract: Doped tin dioxide (SnO 2 ) is an important semiconductor that is already used in diverse applications. However, to determine the entire potential of this material in more advanced applications of optoelectronics, further improvements in electrical properties are necessary. In this work, we perform an extensive search for useful substitutional dopants of SnO 2 . We use a well-converged protocol to scan the entire periodic table for dopants, finding excellent agreement between our predictions and those substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…Studies of a similar nature on Sn-based transparent conductors have been demonstrated to agree with experimental observations. 46,47 While we found multiple donor impurities, which would not be detrimental to the transparency of CuI, self-consistent Fermi level evaluation revealed that ambipolar behavior in this material is unlikely to be achieved experimentally. This is a direct consequence of the low formation energy of the compensating native copper vacancy, that is expected to start forming spontaneously E F Dx o 0 eV with increasing Fermi level, regardless of Cu-or I-rich environments.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Studies of a similar nature on Sn-based transparent conductors have been demonstrated to agree with experimental observations. 46,47 While we found multiple donor impurities, which would not be detrimental to the transparency of CuI, self-consistent Fermi level evaluation revealed that ambipolar behavior in this material is unlikely to be achieved experimentally. This is a direct consequence of the low formation energy of the compensating native copper vacancy, that is expected to start forming spontaneously E F Dx o 0 eV with increasing Fermi level, regardless of Cu-or I-rich environments.…”
Section: Discussionmentioning
confidence: 77%
“…To evaluate efficiently the formation energies of all 64 candidate elements considered in this study, we performed a pre-screening step using the PBE semi-local exchange-correlation functional, following the approach in ref. 46. Such a step has been shown to be highly effective in dopant searches in other TCMs.…”
Section: Screening Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a few promising theoretical hints, this strategy of use doping at high pressure is at early stages of development both experimentally and computationally: Experimentally one faces with the problem that methods for doping under pressure have not being developed, thus it still remains a challenge in the field of semiconductors [489]. Computationally, one faces with the problem of accessing the "doping space" of materials which requires to apply systematic and well-converged protocols to scan for suitable dopants [490], establishing properties and stability of dopants. At zero pressure and for semiconducting systems accurate estimations [491,492] can be obtained but are intrinsically difficult to compute.…”
Section: Optimizing Tc and Pressure In Hydridesmentioning
confidence: 99%
“…All formation energies were first evaluated with PBE level of theory and if either acceptor or donor behavior was identified, a subsequent hybrid functional calculation cycle was performed to verify the result. The choice of PBE prescreening for TCO materials is justified and demonstrated elsewhere [23].…”
Section: A Defect Calculationsmentioning
confidence: 99%